2013
DOI: 10.1093/jnci/djt235
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Cervical Cancer Precursors With p16/Ki-67 Dual-Stained Cytology: Results of the PALMS Study

Abstract: BackgroundPap cytology is known to be more specific but less sensitive than testing for human papillomavirus (HPV) for the detection of high-grade cervical intraepithelial neoplasia (CIN2+). We assessed whether p16/Ki-67 dual-stained cytology, a biomarker combination indicative of transforming HPV infections, can provide high sensitivity for CIN2+ in screening while maintaining high specificity. Results were compared with Pap cytology and HPV testing.MethodsA total of 27349 women 18 years or older attending ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
193
2
14

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(224 citation statements)
references
References 27 publications
15
193
2
14
Order By: Relevance
“…10,17 Recently, the combination of p16 and Ki67 detected by immunohistochemistry has been used in cytological samples to identify patients with high-grade cervical lesions. 18,19 In our study, the analysis of these biomarkers in biopsy material by immunohistochemistry showed that all were positive in a high proportion of the HSIL lesions, which is consistent with current evidence. 8,16,[20][21][22][23] Nevertheless, immunohistochemistry is not adequate for screening purposes.…”
Section: Discussionsupporting
confidence: 92%
“…10,17 Recently, the combination of p16 and Ki67 detected by immunohistochemistry has been used in cytological samples to identify patients with high-grade cervical lesions. 18,19 In our study, the analysis of these biomarkers in biopsy material by immunohistochemistry showed that all were positive in a high proportion of the HSIL lesions, which is consistent with current evidence. 8,16,[20][21][22][23] Nevertheless, immunohistochemistry is not adequate for screening purposes.…”
Section: Discussionsupporting
confidence: 92%
“…The p16/Ki-67 or dual-stain assay has been evaluated in several populations. [9][10][11][12] However, a formal reproducibility analysis of the dual-stain assay has not been reported to date. We conducted a systematic reproducibility analysis of 480 p16/Ki-67 dual-stain cytology specimens among 10 raters in a routine US cytology practice compared with an expert evaluation and assessed clinical performance between the evaluators for the detection of cervical intraepithelial neoplasia grade 2 or greater (CIN21).…”
Section: Introductionmentioning
confidence: 99%
“…A study that looked at the dual stained cytology of p16/Ki-67 showed these markers have superior sensitivity with noninferior specificity with that of Pap cytology when screening for CIN2. 4 However, this testing currently is not FDA approved for routine screening.…”
Section: Discussionmentioning
confidence: 99%